Distinguish Between Perforation or Coronary Cameral Fistula: A Rare Findings during Percutaneous Coronary Intervention - Sidhi Laksono; Irwan Surya Angkasa; Tonni Zheng; Cliffian Hosana; Putri Nurbaeti; Endin Nokik Stujanna (The Avicenna Medical Journal, 2025)
Introduction: Coronary cameral fistula (CCFs) is a connection between the coronary arteries and a chamber of the heart. Most of it is accidentally found on coronary angiography. This case report discusses a patient with symptoms in whom CCF was incidentally found on CAG. Case presentation: A 49-year-old male patient came to our hospital to undergo an elective standby coronary angiogram. No plaque was found in the LM and LCx; however, a chronic total occlusion (CTO) in the medial LAD was found, as well as 60% tubular stenosis in the proximal and 75% tubular stenosis in the distal RCA. Drug eluting stent was placed up to 20 atm in mid-distal LAD. However, we found contrast-dye extravasation that emptied directly into the heart chamber from the distal LAD. There’s no any signs of pericardial effusion from the bedside echo thus reinforcing the diagnosis of CCFs. Discussion: CCFs represent rare cardiovascular anomalies characterized by abnormal connections between coronary arteries and cardiac chambers or major vessels. Conclussion: Bedside echocardiography is a rapid modality to differentiate perforation from CCFs and can be performed intra-PCI. Management such as transcatheter closure or surgical ligation, can be performed with their own indications.